Synthesis and easy intramolecular cyclization in a number of aspartyl derivatives of histamine - G. A. Zheltukhina; E. I. Efimova; T. A. Kromova; V. E. Nebolsin (Тонкие химические технологии, 2006)
A series of natural and novel aspartyl derivatives of histamine were obtained by the classical peptide chemistry methods in a solution. During the synthesis of Nacetylaspartylhistamine easy and spontaneously cyclization of the protected Ac-AspOBzl into succinimide derivative was observed even after one day storage.